MOISTURE SORPTION BEHAVIOR OF JATROPHA SEEDS AT 20 °C AS A SOURCE OF VEGETABLE OIL FOR BIODIESEL PRODUCTION - Ika Amalia Kartika (Jurnal Teknologi Industri Pertanian, 2009)
This research studied the moisture sorption behavior of jatropha seeds by developing a model that correlates the equilibrium moisture (EMC) and Free Fatty Acids (FFA) contents as a function of water activity and EMC, respectively. Two sets of sorption-isotherm experiments were performed to describe the relationship of EMC and FFA contents with water activity, both for fresh and dried seeds of Banten and Lampung varieties. The seeds are conditioned in a series of vessel with saturated salts at certain water activity. The EMC were increased following an increase in water activity in either desorption or adsorption. The hysteresis effect is more pronounced at Banten variety than Lampung one. The FFA content of fresh seeds was increased with an increase in water activity, while the FFA content of dried seeds is relatively constant. The moisture sorption behavior of jatropha seeds reveals that like most product, it exhibits the sigmoid pattern. The BET, GAB, Harkins-Jura, Halsey and Oswin models are recommended to be adequate in predicting the amount of moisture adsorbed or desorbed at known humidity. The relationship between EMC and FFA contents shows that the polynomial equation is the best for fresh seeds, and constant equation for dried seeds.Keyword: moisture sorption; jatropha seeds; water activity; equilibrium moisture content;